Fecal Microbiota Transplant in Severe/Complicated Clostridium difficile Infection: A Retrospective Case Series. Issue 5 (September 2017) - Gundacker, Nathan D.; Walker, Jeremey B.; Rodriguez, J. Martin; Morrow, Casey D.
Abstract : Abstract: Clostridium difficile infection (CDI) is the most common hospital-acquired infection in the United States. Fecal microbiota transplant (FMT) has become a highly efficacious therapy for recurrent mild/moderate disease; however, the efficacy and optimal delivery method in severe/complicated disease is unknown. A retrospective chart review was performed for all FMT recipients at the University of Alabama at Birmingham. Those with severe/complicated disease were isolated and their clinical course documented via chart review and phone calls. Eight patients with severe/complicated CDI who received FMT via both lower and/or upper routes were documented. Six experienced eventual cure, 2 died, with 1 death attributed to CDI, the other to another nosocomial infection. Fecal microbiota transplant is a reasonable option and should be considered in patients who are not surgical candidates. If lower endoscopy is not possible, delivery of FMT via nasogastric tube should also be considered. More studies comparing the efficacy of these routes are needed. Abstract : Severe Clostridium difficile infection is often difficult to manage. This article describes fecal microbiota transplant (FMT) in 8 patients who were not surgical candidates and had failed medical therapy. Six of eight were cured with FMT. FMT should be considered in those with severe disease, especially if they are not candidates for other therapies.